Nursing Students Perceptions of Using YouTube to Teach Psychomotor Skills: A Comparative Pilot Study - Richard Burton DNP, MSN, BSN, CMSRN (SAGE Publishing, 2022)
Introduction Current techniques to teach psychomotor skills to nursing students involve the traditional modeled performance by an instructor followed by rote memorization and practice. This outdated model presents many issues including no reference to refer back to, lacks technology integration, and only meets a few learning styles. A developmental study utilizing the social media platform YouTube was examined to gain student's perspective on this as a teaching tool to assist in skill acquisition. Objective Do nursing students, who are enrolled in a Bachelor of Science Nursing (BSN) program and who are taught psychomotor nursing skills via demonstration on the social media platform YouTube, prefer this technology to traditional demonstration, and to evaluate their overall perceptions of YouTube? Methods Data collection was done utilizing a nursing cohort enrolled in a BSN program. Participants were split into two groups. The control group was taught intravenous (IV) skills in the traditional teacher demonstration followed by practice. Experimental group was given access to a YouTube video series consisting of the identified IV skills. After testing for competency was concluded, control group was given access to the videos. A questionnaire was developed and sent out for evaluation. Results Participants reported that their preferred learning style when learning new nursing skills was visual (41.7%) followed by a combination of visual, tactile, and auditory (41.7%). All respondents (100%) reported YouTube videos increased their learning. Respondents (100%) also noted that having access to the videos better prepared them. In experimental group, all participants (100%) watched the videos, and in the control group, only (16.7%) of students watched the videos after the skill had been learned. Conclusion Results demonstrated that students prefer YouTube videos when learning new skills. They reported feeling better prepared to learn. YouTube is a potential way to increase skill acquisition and integrate technology into the nursing curriculum.